Irreversible bonds for higher stability of COF materials in photocatalytic reactions - Ma, Fang; Ye, Liqun (Frontiers in Fuels, 2024)
Covalent organic frameworks (COFs), one out of a multitude of advanced mainstream materials in photocatalysts, were crystalline porous materials with tunable topology, highly porous and connected by dynamic covalent bonds. It was well known that efficient photocatalytic yields were what we ultimately wanted to achieve, consequently, the stability of the bond energy was crucial. Stable bond energy will make our products in the application to reduce unnecessary economic lessen. At present, the main photocatalysts were the reversible imine bonds and other 2DCOFs, but the irreversibly stable COFs were seldom involved. Therefore, the purpose of this review which provides superficial opinions for the majority of scholars to explore the stability of irreversible bond energy, elaboratting the synthesis schemes and synthesis ideas of irreversible bonds in partly published. The irreversibly connected bond will improve the stability and durability of our synthesized catalyst in practical applications, therefore, it has great benefit to explore the stability of bond energy for our practical applications. In this review, we mainly summarized in detail the irreversible bonding pattern, exploring the stability of COFs, summarizing classic highly crystalline ordered semiconductor materials that have been published COFs with irreversible bonding methods at the present stage.